APAKAH PROFESIONALISME, KOMPETENSI, DAN PENGALAMAN AUDITOR DAPAT BERPERAN DALAM MENDETEKSI KECURANGAN? - Arafah, Fauziah Nur; Suparno, Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to analyze the role of professionalism, competence, and experience of auditors in detecting fraudulent acts in the financial statements of the BPK RI Representative Office of Aceh. Data was collected by distributing questionnaires to 76 BPK RI Representative Office of Aceh auditors. Data were analyzed using multiple linear regression analysis methods, consisting of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, hypothesis test, partial test, and simultaneous test, then processed using statistical products and solution software programs service (SPSS version 24). The results show that professionalism plays a role in detecting fraud, while competence and work experience do not play a role in detecting fraud. In addition, professionalism, competence, and experience simultaneously affect fraud detection.